Microstructural and wear behaviour of heat treated Cu-11Ni-6Sn alloy. (2020) - Sathishkumar, G.; Saravanan, S.; Navaneethakrishan, G.; Parkunam, N.; Yokeshwaran, R.
Abstract: Cu-11Ni-6Sn alloy used bearing material in aerospace and mining industries, Casting is one of the famous metal additive process in which it is able to produce complex shape for engineering applications. Heat Treatment is the controlled heating and cooling of metals to modify their physical and mechanical properties. In the present study, to investigate the microstructural and wear behaviour of heat treated Cu-11Ni-6Sn alloys. During the aging process, the hardness of the alloy increased, which is due to microstructural changes. The wear rate is a function of hardness of the alloy decreased and it follows the adhesion theory of wear.